Baseline (18)F-FDG PET image-derived parameters for therapy response prediction in oesophageal cancer - Hatt, Mathieu (Springer-Verlag Berlin, 2011)
BACKGROUND: The objectives of this study were to investigate the predictive value of tumour measurements on 18F-FDG PET pretreatment scan regarding therapy response in oesophageal cancer and to evaluate the impact of tumour delineation strategies. METHODS: 50 patients with oesophageal cancer treated with concomitant radio-chemotherapy between 2004 and 2008 were retrospectively considered and classified as complete, partial or non responders (including stable and progressive disease) according to RECIST. The classification of partial and complete responders was confirmed by biopsy. Tumours were delineated on the 18F-FDG pretreatment scan using an adaptive threshold and the automatic Fuzzy Locally Adaptive Bayesian (FLAB) methodologies. Several parameters were then extracted: maximum and peak SUV, tumour longitudinal length (TL) and volume (TV), mean SUV, and Total Lesion Glycolysis (TLG=TV×mean SUV). The correlation between each parameter and response was investigated using Kruskal-Wallis tests and receiver operating characteristic methodology was used to assess performance of the parameters to differentiate patients. RESULTS: Whereas commonly-used parameters such as SUV measurements were not significant predictive factors of the response, parameters related to tumour functional spatial extent (TL, TV, TLG) allowed significant differentiation of all three groups of patients, independently of the delineation strategy, and could identify complete and non responders with sensitivity above 75% and specificity above 85%. A systematic although not statistically significant trend was observed regarding the hierarchy of the delineation methodologies and the considered parameters, with slightly higher predictive value obtained with FLAB over adaptive thresholding, and TLG over TV and TL. CONCLUSIONS: TLG is a promising predictive factor of concomitant radio-chemotherapy response with statistically higher predictive value than SUV measurements in advanced oesophageal cancer.